Pemanfaatan Media PhET untuk Meningkatkan Minat dan Aktivitas Belajar IPA Siswa Kelas V Sekolah Dasar - Fitriyah Ika Astutik (Khatulistiwa Insight: Islamic Education and Learning, 2026)
This study aims to analyze the utilization of PhET (Physics Education Technology) media to enhance students’ interest and learning activity in science subjects among fifth-grade students at SDN Waru Barat 4, focusing on the topic of “Force and Energy.” The research was motivated by the low level of student engagement in science learning, often caused by the dominance of conventional, teacher-centered instruction. A quantitative approach using Classroom Action Research (CAR) with the Kemmis and McTaggart model was employed, conducted in two cycles. The research subjects consisted of 25 fifth-grade students during the first semester of the 2025/2026 academic year. Data were collected through observation, learning interest questionnaires, and interviews, then analyzed using descriptive quantitative methods. The findings revealed a significant improvement in students’ learning interest and activity. The average learning interest score increased from 67.4 to 88.6, while the learning activity score rose from 69.2 to 91.8. Moreover, students demonstrated better conceptual understanding of the relationship between force, mass, and kinetic energy. The use of PhET simulations not only enhanced engagement and curiosity but also fostered intrinsic motivation and self-confidence. Therefore, PhET media proved to be an effective tool for promoting active, collaborative, and meaningful science learning in elementary education.